The effect of muscle fatigue on the last stride before stepping down a curb - Barbieri, Fabio Augusto [UNESP]; Lee, Yun-Ju; Gobbi, Lilian Teresa Bucken [UNESP]; Pijnappels, Mirjam; Van Dieën, Jaap H. (Elsevier, 2013)
The stride before landing may be important during stepping down. The aim of this study was to analyze variability of the kinematics and muscle activity in the final stride before stepping down a curb, with and without ankle and knee muscle fatigue. Ten young participants walked at self-selected speed and stepped down a height difference (10-cm) in ongoing gait. Five trials were performed before and after a muscle fatigue protocol (one day: ankle muscle fatigue, another day: knee muscle fatigue). The analysis focused on the trailing leg during the last but one and the last step on the higher level. Kinematics and muscle activity were recorded. Fatigue increased variability of foot-step horizontal distance in the last step on the higher level of the trailing limb, as well as in the first steps on the lower level for both limbs. This appeared due to an increase in the range of motion of the knee joint after both fatigue protocols. Participants additionally showed an increased ankle and hip ROM and decreased knee ROM. Our results suggest a loss of control under fatigue reflected in a higher variability of trailing and leading limb-step horizontal distances, with compensatory changes to limit fatigue effects, such as a redistribution of movement over joints. © 2012 Elsevier B.V.
Keywords: Muscle fatigue; Stepping down; Variability; Walking; adult; ankle; clinical article; controlled study; gastrocnemius muscle; hip; human; joint function; kinematics; knee; limb movement; muscle fatigue; muscle function; priority journal; range of motion; rectus femoris muscle; task performance; tibialis anterior muscle; walking; walking speed; Adult; Ankle Joint; Biomechanics; Gait; Hip Joint; Humans; Knee Joint; Muscle Fatigue; Muscle, Skeletal; Range of Motion, Articular; Young Adult